2019 International Conference on Process Mining (ICPM) 2019
DOI: 10.1109/icpm.2019.00020
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Software Development Teams' Efficiency using Process Mining

Abstract: Context. Improving the efficiency and effectiveness of software development projects implies understanding their actual process. Given the same requirements specification, different software development teams may follow different strategies and that may lead to inappropriate use of tools or non-optimized allocation of effort on spurious activities, non-aligned with the desired goals. However, due to its intangibility, the actual process followed by each developer or team is often a black box.Objective. The ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…The aim is to retrieve control-flow and structural aspects of software development cycles from existing data sources and software repositories. As a result, Bug trackers, version control systems, and mail archives are related to tracking software development events [6][7][8][9][10][11][12][13].…”
Section: First Category Of Pm For Software Developmentmentioning
confidence: 99%
“…The aim is to retrieve control-flow and structural aspects of software development cycles from existing data sources and software repositories. As a result, Bug trackers, version control systems, and mail archives are related to tracking software development events [6][7][8][9][10][11][12][13].…”
Section: First Category Of Pm For Software Developmentmentioning
confidence: 99%
“…[Ru07] identified the possibility of a 'faster PMS creation'. [Ru14b] suggested to embed the model into the development lifecycle due to effectiveness, [Ca19] found that their model accuracy was sufficient. The other works did at least not falsify this assumption and presented theoretical or practical benefits e.g.…”
Section: Detailed Findings From Primary Studiesmentioning
confidence: 99%
“…A development session executed by one developer at his/her IDE can be considered an instance of a process, where the goal is to produce a software product or maintain an existing one. Its workflow of activities depends on many factors, such as the development methodology, program design or individual experience [10]. Furthermore, developers are usually free to produce code without a referential model or guidelines on how to execute the coding tasks and, most often without any intelligent guidance from traditional development tools.…”
Section: Motivationmentioning
confidence: 99%